CIDARC, another source of information on tropical agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In Montpellier, France, CIRAD has recently established the International Centre for Documentation on Hot Climate Agriculture (CIDARC), which has brought together all the documentation resources previously held by its different departments. These...